FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN KB SUNTIK DI WILAYAH KERJA PUSKESMAS KABAWO - Taher, Rusli; Yana, Putri (Pasapua Health Journal, 2020)
Introduction : The Family Planning Movement (KB) in Indonesia has become an example of how the country with the fourth largest population in the world can control and accept the family planning movement as a form of family development that is more manageable to achieve prosperity. This study aims to determine the target of the meeting with knowledge, previous assessments, husband’s support, and affordability of services with an increase in injecting family planning acceptors. Method : This type of research is analytic research using cross sectional, participation in this study was 152 acceptors, taking samples using purposive sampling obtained 111 samples of acceptors. Data were analyzed univariately and bivariately. Results: Univariate analysis, injecting family planning acceptors with 100 injections (90.09%), and non-injection injections 11 (9.91), knowledge, both 55 people (49.55%), less than 56 people (50.45%), findings Previously, contraception, AMK 54 (57.66%), AP / AK 47 people (42.34%), husband’s support, supporters79 (71.17%), did not support 31 (28.83%), involvement of assistance outreach, easily obtained 43 (38.74%), practical / easy 68 people (61.26%). The results showed that there was a significant relationship between knowledge, experience, husband’s support, and service affordability with contraceptive selection where the p value <0.05. Conclusion: there is a relationship of knowledge, experience, husband’s support, and affordability of services in the working area of the district health center of Kabawo, Laimpi district, district of Mawata district, Muna district in 2019.